A Novel 167‐Amino Acid Protein Encoded by CircPCSK6 Inhibits Intrahepatic Cholangiocarcinoma Progression via IKBα Ubiquitination - Canghai Guan; Jianjun Gao; Xinlei Zou; Wujiang Shi; Yunhe Hao; Yifei Ge; Zhaoqiang Xu; Chengru Yang; Shaowu Bi; Xingming Jiang; Pengcheng Kang; Xiaoxue Xu; et al. (Advanced Science)
Abstract Intrahepatic cholangiocarcinoma (ICC), a formidable challenge in oncology, demands innovative biomarkers and therapeutic targets. This research highlights the importance of the circular RNA (circRNA) circPCSK6 and its peptide derivative circPCSK6‐167aa in ICC. CircPCSK6 is significantly downregulated in both ICC patients and mouse primary ICC models, and its lower expression is linked to adverse prognosis, highlighting its pivotal role in ICC pathogenesis. Functionally, this study elucidates the regulatory effect of circPCSK6‐167aa on IκBα ubiquitination within the NF‐κB pathway, which is mediated by its competitive binding to the E3 ligase RBBP6. This complex interaction leads to reduced activation of the NF‐κB pathway, thereby curbing tumor cell proliferation, migration, invasion, stemness, and hepatic‐lung metastasis in vivo. This groundbreaking discovery expands the understanding of circRNA‐driven tumorigenesis through atypical signaling pathways. Additionally, this investigation identified EIF4A3 as a detrimental regulator of circPCSK6, exacerbating ICC malignancy. Importantly, by leveraging patient‐derived xenograft (PDX), organoids, and organoid‐derived PDX models, higher levels of circPCSK6‐167aa enhance sensitivity to gemcitabine, indicating its potential to improve the effectiveness of chemotherapy. These insights emphasize the therapeutic promise of targeting circPCSK6‐167aa, offering vital biological insights and clinical directions for developing cutting‐edge therapeutic approaches, thus revealing innovative strategies and targets for future treatments.